Home nursing assistance and care in a pandemic time (Research, Society and Development, 2022)
Objective: to analyze the scientific publications related to the home care of nurses in times of a pandemic of COVID-19. Methodology: This is an integrative literature review. For the elaboration of the integrative review, the steps described below were considered: construction of the guiding question, definition of inclusion and exclusion criteria, selection and search of studies in the databases, extraction of information, categorization and evaluation of studies included in the review, analysis and synthesis of data, presentation of the review. The studies obtained were evaluated by the level of scientific evidence. Results: The selection of articles followed the PRISMA recommendation, the search carried out had a total of 58 articles that after selection three articles made up the review. Conclusion: This research was based on reading scientific articles, which shows the relevance of home care and assistance, for the elaboration of the individual and collective care plan, and to create a strategy to work with the area of ​​coverage.